Prövad eller beprövad? Praktiker för prövande av lärares yrkeserfarenheter i skolan - Åman, Pia; Lindberg, Ylva; Rapp, Stephan (Educare, 2021)
The rationale for this study stems from the Swedish educational context, where teacher practice is subject to policies stating that education must be built on research foundation and proven experience. In a previous article (Åman & Kroksmark, 2018), we demonstrated that the research foundation is operating in concurrence of teachers’ practices and experiences. This study in turn aims to explore how teachers understand proven experience and practices of proving professional experiences. The data was collected in 2014 in the project Modellskolan [The Model School], financed by the Swedish Research Council, through a stimulated recall method. We filmed 14 interviews with teachers focusing on group discussions about teachers’ practical dilemmas. The interviews were analyzed with a phenomenographic method, and the result revealed five categories with which the teachers evaluated collegial and individual experiences. The categories were analysed through praxis theory and linked to the phenomenological concepts of time and space to elucidate how fluid situated and unspoken professional experiences become systematic, general and partly transferable through proving practices. The results shed light on how teachers’ experiences and everyday practices challenge and encourage revisions of the definitions of research foundation and proven experiencea in Swedish national policies.